ANALISIS PENERAPAN TRANSAKSI IJARAH DAN AL IJARAH AL MUNTAHIYA BIT TAMLIK PADA BANK SYARIAH - Ali Muhayatsyah (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2019)
This study was conducted to investigate how the implementation of ijarah and Al Ijarah al Muntahiya bit Tamlik (IMBT) transactions in Islamic banks. The application of lease transactions with ijarah and IMBT schemes on Islamic bank products is in accordance with Islamic principles. The basis of the implementation of ijarah transactions in Islamic banks refers to the rules of the Fatwa of the National Sharia Board of the Indonesian Ulema Council (DSN-MUI) and Supreme Court Regulation No. 2 of 2008 on Compilation Islamic Economic Law (KHES). There are differences regarding the implementation of the transfer of ownership of the object of lease on IMBT, the transfer of the object of the lease can only be carried out if the ijarah agreement has been completed, the option to transfer the object of the leased object can be done with the promise (wa'ad) of buying and selling. So there is no regulation regarding IMBT contract based on the transfer of ownership of the object with the promise (wa'ad) of the grant, it is contradictory because there is a reward that must be given by the customer (mustajir) to the bank for the IMBT contract object.